Pesquisa em história da educação no Brasil - Gomes, Adriana Rodrigues; Ribeiro, Andreza Karla de Souza; Pereira, Mariana Nogueira (Revista Educação em Questão, 2007)
GONDRA, José Gonçalves. (Org.). Pesquisa em história da educação no Brasil. Rio de Janeiro: DP&A, 2005.